Economic implications of transport on the Nigerian economy: A study of road transport choice and cost of doing business - Purokayo, Gambiyo Suleiman (2015)
Transportation infrastructure is vital for growth of economies worldwide, and for developing-country catch-up drive. The objective of this study is to examine the current state of road transport infrastructure with emphasis to travel choice and its impacts on the cost of doing business. Data was sourced from some locations in the Northeast Nigeria. Two main theories formed the springboard of this study: public finance theory, and infrastructure theories. Multinomial logit and ordinary least square (OLS) are the main tools of analysis. The results of multinomial logit (marginal effects) show that worsening conditions in the terrain affects transport choice, preference of individuals and cost of doing business. This has implications of price of transportation, agricultural productivity, and cost of transactions. OLS results for public investment and maintenance estimated showed low investment expenditure on roads due to fiscal problems.This has generally effected cost of doing business manifested in high transport prices, prices of goods and services. These results are supported by findings of World Bank, Sub-Saharan Africa Transport Policy and others agencies. Nigeria’s infrastructure deficit remains one of the binding constraints to growth in the economy. The overall marginal change in network access showed increased access due to new highways. However these gains have not been sustained due crisis in the locations. Participation of the private sector is road building is still very low to compliment public expenditure. The study recommends higher prioritization for roads in the budget space; this supports the goals of the national transport policy of 2010, that 90 percent of all movement of goods and people is by road transportation